How do Capital Controls Affect the Transmission of Foreign Shocks? - Dudley Cooke (University of Copenhagen, Economic Policy Research Unit (EPRU), 2007)
This paper studies the short-run transmission of foreign shocks in a small open economy with capital controls and a fixed exchange rate. Capital controls alter the transmission of shocks because endogenous changes in the domestic nominal interest rate affect savings and investment decisions. The economy's reaction to export shocks hinges on how the government chooses to restrict capital flows; that is, whether inflows or outflows are restricted. For foreign interest rate shocks, private capital flows are important, but so are the government's holdings of foreign exchange reserves. Finally, a simple graphical apparatus is developed to provide a contrast to the case when capital flows are unrestricted.
Keywords: E58; F32; F41; 330; capital controls; foreign shocks; Kapitalverkehrskontrolle; Schock; Spillover-Effekt; Kleine offene Volkswirtschaft; Theorie